Oral Paricalcitol Reduces the Prevalence of Posttransplant Hyperparathyroidism: Results of an Open Label Randomized Trial - Amer, H.; Griffin, M. D.; Stegall, M. D.; Cosio, F. G.; Park, W. D.; Kremers, W. K.; Heilman, R. L.; Mazur, M. J.; Hamawi, K.; Larson, T. S.; Kumar, R. (American journal of transplantation, 2013)
Postkidney transplant hyperparathyroidism is a significant problem. Vitamin D receptor agonists are known to suppress parathyroid hormone (PTH) secretion. We examined the effect of oral paricalcitol on posttransplant secondary hyperparathyroidism by conducting an open label randomized trial in which 100 incident kidney transplant recipients were randomized 1:1 to receive oral paricalcitol, 2 μg per day, for the first year posttransplant or no additional therapy. Serial measurements of serum PTH, calcium and bone alkaline phosphatase, 24‐h urine calcium and bone density were performed. The primary endpoint was the frequency of hyperparathyroidism 1‐year posttransplant. Eighty‐seven patients completed the trial. One‐year posttransplant, 29% of paricalcitol‐treated subjects had hyperparathyroidism compared with 63% of untreated patients (p = 0.0005). Calcium supplementation was discontinued in two control and 15 treatment patients due to mild hypercalcemia or hypercalcuria. Paricalcitol was discontinued in four patients due to hypercalcuria/hypercalcemia and in one for preference. Two subjects required decreasing the dose of paricalcitol to 1 μg daily. Hypercalcemia was asymptomatic and reversible. Incidence of acute rejection, BK nephropathy and renal function at 1 year were similar between groups. Moderate renal allograft fibrosis was reduced in treated patients. Oral paricalcitol is effective in decreasing posttransplant hyperparathyroidism and may have beneficial effects on renal allograft histology. Paricalcitol decreases the prevalence of post‐kidney transplant hyperparathyroidism and may have beneficial effects on renal allograft histology.